2022
DOI: 10.22323/2.21070201
|View full text |Cite
|
Sign up to set email alerts
|

Exploring scientists’ perceptions of citizen science for public engagement with science

Abstract: It is often assumed that citizen science is inherently participatory in nature. However, citizen science projects exist along a continuum from data contribution to full co-creation. We invited 19 biologists to explore their conceptions of citizen science. Almost all participants defined citizen science as involving non-scientists in data collection. This definition acted as a barrier for scientists who did not see how citizen science could suit their research objectives. While interviewees perceived many socie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…The demonstration of the ECS's reliability is important, as there is a negative stigma around citizen science data [25]. Our results are consistent with prior work that has shown that such data can be of a high quality [26][27][28]. The development and design of the tool likely contributed to its reliability.…”
Section: Discussionsupporting
confidence: 84%
“…The demonstration of the ECS's reliability is important, as there is a negative stigma around citizen science data [25]. Our results are consistent with prior work that has shown that such data can be of a high quality [26][27][28]. The development and design of the tool likely contributed to its reliability.…”
Section: Discussionsupporting
confidence: 84%
“…This supports evidence that citizen science as a research approach has the potential to actively engage and involve the public at every stage of research, beyond data collection (62). Though evidence shows that the level of involvement and participation of citizen scientists is dependent on the purpose and objective of the project design, type of research question, and available resources (63). The characteristics of citizen science projects also influence the intensity of citizens' engagement, participation and geographical sampling frame (64).…”
Section: Discussionmentioning
confidence: 63%
“…Therefore, in starting a discussion around the ethical, legal and safeguarding issues that might arise as a result of online citizen science projects we are proposing the best practice guideline for mental health citizen science projects (Table 5). The use of a best practice guideline is important in building trust with communities and support for citizen science project designers (63). All the studies included in our review were conducted in highincome countries.…”
Section: Discussionmentioning
confidence: 99%
“…This helps to fill knowledge gaps and provide essential information for decision-making processes, such as policymaking and resource allocation. Second, citizen science fosters public engagement in science, and scientific literacy [11], developing a deeper understanding of scientific concepts and methodologies. on citizen science platforms, they consistently contribute mainly to a select few on a regular basis.…”
Section: Introductionmentioning
confidence: 99%